2014
DOI: 10.1039/c3nr05539f
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient colorimetric detection of target cancer cells utilizing superior catalytic activity of graphene oxide–magnetic-platinum nanohybrids

Abstract: Enzyme-linked immunosorbent assays (ELISAs) have most widely been applied in immunoassays for several decades. However, several unavoidable limitations (e.g., instability caused by structural unfolding) of natural enzymes have hindered their widespread applications. Here, we describe a new nanohybrid consisting of Fe₃O₄ magnetic nanoparticles (MNPs) and platinum nanoparticles (Pt NPs), simultaneously immobilized on the surface of graphene oxide (GO). By synergistically integrating highly catalytically active P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
0
3

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 100 publications
(66 citation statements)
references
References 41 publications
0
63
0
3
Order By: Relevance
“…[116,117,127,134,155] Song et al first reported af olic acidconjugated graphene-hemin hybrid (GFH) for selective, quantitative,a nd fast colorimetric detection of cancer cells by using its peroxidase-like activity (Figure 7a). [116,117,127,134,155] Song et al first reported af olic acidconjugated graphene-hemin hybrid (GFH) for selective, quantitative,a nd fast colorimetric detection of cancer cells by using its peroxidase-like activity (Figure 7a).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…[116,117,127,134,155] Song et al first reported af olic acidconjugated graphene-hemin hybrid (GFH) for selective, quantitative,a nd fast colorimetric detection of cancer cells by using its peroxidase-like activity (Figure 7a). [116,117,127,134,155] Song et al first reported af olic acidconjugated graphene-hemin hybrid (GFH) for selective, quantitative,a nd fast colorimetric detection of cancer cells by using its peroxidase-like activity (Figure 7a).…”
Section: Methodsmentioning
confidence: 99%
“…Besides their intrinsic enzymatic activity,CNMs and their derivatives can be also utilized as modulators to further improve the catalytic activity and stability of artificial peroxidase.M any classic artificial peroxidases,f or instance, metal oxides (for example,F e 3 O 4 , FeO x H, [94] Fe 2 O 3 , [95][96][97] Co 3 O 4 , [98][99][100] ZnO, [101] CuO, [102][103][104][105] Cu 2 O, [106] CeO 2 , [92] Co-Fe 2 O 4 , [107,108] and WO 3 [109] ), metal hydroxide, [110] metal chalcogenides (for example,C oSe 2 , [111] CuS, [112,113] and MoS 2 [114] ), metal nanoparticles (for example,P t, [92,[115][116][117][118][119][120][121] Pd, [82,88,122,123] Au, [84,88,[124][125][126][127][128][129][130][131][132][133]…”
Section: Cnms As Modulators In Hybrid Artificial Peroxidasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Fe 3 O 4 nanoparticles were synthesized by a solvo-thermal method (Deng et al, 2005) (see SI), Graphene Oxide (GO) was prepared using a modified Hummer’s method (SI) (Kim et al, 2014; Hummers and Offeman, 1958). Briefly, 50 mg of Fe 3 O 4 nanoparticles were sonicated 5 min with 10 mL 0.1 mg/mL poly(diallydimethylammonium chloride) (PDDA) in water, magnetically separated, washed 3x with water, and re-suspended in 25 mL water.…”
Section: Methodsmentioning
confidence: 99%
“…Recent research has looked to explore innovative and powerful functionalized nanostructures by controlling and tailoring their properties in a very predictable manner to meet the requirement of specific applications [13][14][15]. Kim et al designed a highly efficient enzyme-free colorimetric detection of target cancer cells utilizing superior catalytic activity of graphene oxide-magnetic-platinum nanohybrids [16]. Vabbina et al.…”
Section: Introductionmentioning
confidence: 99%